The man who mistook his wife for a hat and other clinical tales [compact disc, unabridged] - Sacks, Oliver, 1933-2015 (Brilliance Audio, 2011)
Oliver Sacks recounts the case histories of patients living in the bizarre world of neurological disorders. This book tells the stories of individuals afflicted with great perceptual aberrations, patients who have lost their memories, and those who are no longer able to recognize people and common objects. They are studies of life struggling against incredible adversity.